Monitoring the Status of the Pride Gear Box Using the Beta-Kurtosis of Its Vibrating Signals - Dadkhah Laleh, Alireza; Ettefagh, Mirmohammad; Hasanezhad Qadim, Reza (Revista Publicando, 2018)
Today, with the growth of industry and the increasing development of industrial machinery, the maintenance of these machines and the evaluation of their operation during the work is of particular importance. In this paper, we have tried to find out all the vibration signals associated with it in the case of a healthy and defective gearbox, and to examine the results by familiarizing them with the methods of receiving and analyzing the transmission of the Pride transmission. Using a laboratory gearbox belonging to this vehicle, all of its vibrational signals should be considered. For this purpose, using the vibration sensor, the data is extracted in different operating modes of the machine. After collecting data of each mode, using the MATLAB program and using the Beta-Kurtosis method, one of the statistical methods suitable for diagnosis of the gears will be extracted and examined by the vibration patterns of the transmission of the pride vehicle.